ANALISIS PENGARUH BETA, SIZE, BOOK TO MARKET, DAN PROFITABILITY TERHADAP RETURN AGGRESIVE STOCK (Studi Kasus Pada Indeks Saham Kompas 100 Pada Pasar Modal Indonesia Periode 2009 – 2013) - Baskoro, Yogo Laksono; Sampurno, R. Djoko (Diponegoro Journal of Management, 2015)
Aggressive stocks are stocks that have a high degree of volatility and risk in which this stock has a beta values above one. Which means that stock will increase rapidly if the state of the market has increased, and decreased sharply when the state of the market decline. This study aims to examine the influence of beta, size, market to book ratio, and profitability against aggressive stock return.            The sample used in the study were 15 companies listed in the Indonesia Stock Exchange (BEI), are included in the index are konsiten Compass 100, in the period 2009 to 2013, and has a high beta value of shares (β> 1). The sampling method used in this research is purposive sampling. The analysis technique used in this study is multiple regression, classic assumption test, normality test, multicollinearity, heteroscedasticity test, autocorrelation test, test the coefficient of determination (adjusted R2), the F statistic test, and t statistical test .            These results indicate that beta stocks have a positive and significant impact on aggressive stock returns. Variable size has a negative and significant impact on the variable aggressive stock return. However, there was no significant influence between the variables of market to book ratio and return on equity on stock returns aggressive